Beyond the veil: Unveiling the unconventional - exploring the profiling, attitudes, and influential factors of body donors - Rosemol Xaviour, (Asian Journal of Medical Sciences, 2023)
Background: Cadavers are essential for anatomical education, yet their scarcity plagues medical colleges in Kerala and India. However, the Government Medical College in Thrissur has experienced a rise in annual body donations. Aims and Objectives: This study aims to explore the motivating factors behind this increase among the population of Thrissur. Materials and Methods: This study employed a cross-sectional survey design conducted at the Department of Anatomy, Government Medical College in Thrissur, Kerala. The study utilized data from the Body Donation Register, which covered a period from May 1st, 2011 to April 30th, 2012, encompassing a total of 223 individuals. During this specific period, which was selected due to the notable surge in body donation trends, there was a significant increase observed. The sample size was set at 110 participants. Data collection was conducted through face-to-face interviews with the voluntary body donors and was analyzed using the statistical package for the social sciences, version 16.0. Results: Gender distribution: Among 120 donors, 56.7% were male and 26.7% were female. Age groups 61–70 had the highest percentage (36%) of body donors. Socioeconomic status: the majority were above the poverty line (78.2%). Religious affiliation: Hindus had the largest representation (40 individuals). Marital status: Most donors were married (92 out of 110). Number of children: Most donors had two children (64 individuals). Sources of information: Family and relatives were the primary sources. Awareness of dissection: An equal number of donors were aware and unaware. Motivations for donation varied, including social service and avoiding burden after death. Conclusion: A good proportion of donors had a socioeconomic status above the poverty line, and most of them were graduates or postgraduates. The majority of body donors did not have a religious affiliation. However, they had a strong family background and received support from their families. Interestingly, most of the donors were unaware of how their bodies would be used after donation.